Social media addiction towards young adults emotion / Aina Amiera Abd Rahman and Fariza Hanis Abdul Razak - Abd Rahman, Aina Amiera; Abdul Razak, Fariza Hanis (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
The purpose of this study is to examine if the young adult addicted to social media, analyse if social media addiction will affect their emotion and identify their social media level of addiction. This study is conducted in Universiti Teknologi MARA main campus in Shah Alam. The respondents is 380 student from different type of background, education level and faculty in the university. This study is using Google Forms as the form of online questionnaires. This study revealed that the student level of addiction is mild and not severe. Majority of the student have more than three social media accounts. The most popular social media that they use is Instagram. They spent more than five hours on their social media a day. Although majority of them said that they are addicted to the internet, but there are no sign they have been addicted. The main reason they use social media is for entertainment. The relationship result between social media usage and social media addiction is not significant. But the result between addiction of social media and effect on emotion is significance. It can be concluded that the addiction of social media gave effect on young adults' emotion. It is believed that the obsession toward social media will lead to consequence on young adults' emotion.